Manajemen Kegiatan Ekstrakulikuler dalam Seleksi Santri Berbasis Multiple Intelegence - Abu Hasan Agus R; Fathor Rozi; Faisal Faisal (MANAZHIM, 2023)
The research aims to help the basic problems of students in determining their choice of majors in Extracurriculars by using Multiple Intelligence-based selection. The research was conducted at the Nurul Jadid Islamic Boarding School in the Jalaluddin Ar-rumi area using a qualitative approach with field research. Data obtained from interviews and observations. Data analysis was preceded by interviews with the Head of Santri Resources & Management, chairman of the Association for Organization Rumi (AFORMI), and the students. The results of the study show that the selection of students based on Multiple Intelligence (MI) is very helpful in determining the extracurricular class of the dormitory, it is even very helpful in procuring activities so that the administrators are able to carry out procurement according to the needs of the talents & interests of the students. The stages of the selection implementation consist of conducting questionnaire tests, giving briefings, and delivering material on Multiple Intelligence. The use of Multiple Choice questions was maintained because the administrators considered that the use of these questions was still effective for students. The Multiple Intelligence-based student selection model is very important to develop because Multiple Intelligence emphasizes the individual intelligence of students, which is considered suitable for the current approach to students.